Histopathological evaluation of human amniotic membrane effect on early stage healing of induced defects in rabbit's oral mucosa (Mustansiria Dental Journal, 2018)
This study aims to investigate the role of using dried Human Amniotic Membrane(dHAM) on rabbit's oral mucosal wound healing in its early stages. Six male rabbitswere used in this study. In each rabbit, two elliptical incisions were done on both sidesof tongue dorsum; one of them was left uncovered and the other was covered bydHAM. The animals were divided into two groups with three rabbits each accordingto the sacrifice periods which were three days and one week. After sacrifice,histopathological examination was performed to assess re-epithelialization andinflammation. Within the first three days, the re-epithelialization was much morefaster in dHAM group than that in control one, and the difference between the controland study group was statistically highly significant ( p=0.005